Government Public Communication Management Strategy in Socializing the People's School Policy in Indonesia - Novianty Elizabeth Ayuna (Global Writing Academica Researching and Publishing, 2025)
The People's School Policy—a free, boarding-based education program for low-income families. The success of this policy depends heavily on the effectiveness of information delivery, public acceptance, and community participation. This study aims to analyze the public communication management strategies implemented by the government in its outreach. This research uses a descriptive qualitative approach with a case study method. The results indicate that the government implemented a mixed-method communication strategy, combining direct face-to-face outreach (a community approach) and the use of digital media (social media/websites) for information transparency. The results indicate that the government implemented a single narrative strategy of